The conservation of biodiversity in Malaysia: options for an integrative statutory framework / Sarah Aziz Abdul Ghani Aziz - Sarah Aziz, Abdul Ghani Aziz (2013)
This thesis lies hinged on the conclusion embedded in the National Biodiversity Policy 1998 (“NBP”), that there is no single comprehensive legislation in Malaysia which relates to biological diversity conservation and management as a whole. The NBP goes on to state that the existing legislative framework is sectoral, to an extent restrictive causing some deficiencies, due to an absence of an ntegrative approach across sectors, lacking consideration of the overall objectives of conservation and comprehensive coverage of biological diversity issues. This stems from the provisions of the Constitution of Malaysia 1957 which has unwittingly led to legislative non-uniformity.